What Is Holding Us Together? David Hume, Edgar Allan Poe and the Problem of Association. (2nd July 2022) - Kronfeld, Maya
Abstract: Poe's experimental fiction revitalizes Hume's ambivalent empiricism, the complexities of which were sometimes obscured in the philosopher's nineteenth-century American reception. Poe's 'Murders in the Rue Morgue' broaches formally the question of how one thought leads to another, while 'The Man that Was Used Up' stages the question of what grounds the unity of one's thoughts. Reading both tales together exposes the scope and limits of an associationist paradigm often traced back to Hume. But reading Hume through Poe's verbal art reveals that Hume's 'mitigated scepticism' about personal identity is more difficult to grapple with, and potentially more devastating for Western Reason, than the modes of scepticism that more comfortably entered the English canon. In 'Rue Morgue', Detective Dupin's presumption to reconstruct fully the narrator's train of thought may be the real locus of the tale's horror. In the 'Man that Was Used Up', the heroic General A.B.C. Smith disintegrates on the floor into a talking 'bundle' that parodically literalizes Hume's most famous metaphor in the Treatise . Hume's bundle thus reappears in Poe as the proto-surrealist 'terminus' of a reductive explanation that has become physically real. To say with Hume that the mind is a 'fiction' is not to deny the goings-on of mental phenomena, but to attempt a much more challenging claim: that our minds conceptualize themselves out of their own limited nature, but not in a way that necessarily accords with that nature. If Hume brings out the parody in Poe, we might also say that Poe amplifies the irony in Hume.